Korelasi Teknik Menyusui Ibu dalam Mengaktifkan Hormon Oksitosin terhadap Produksi Air Susu Ibu - Meta Rosdiana; Desi Hariani (Universitas Muhammadiyah Manado, 2025)
Correct breastfeeding technique significantly influences milk production due to the influence of the hormone oxytocin. With the wrong breastfeeding technique, breast milk intake to the baby will not be effective because the baby cannot suckle strongly and slowly, which can hinder the process of breast milk production. Implementing proper breastfeeding technique can facilitate breastfeeding and provide comfort during breastfeeding, thus preventing problems such as soreness and back pain. Examining the correlation between breastfeeding techniques and hormone activation on milk production. This study employed a quantitative analytical design using primary data through a cross-sectional approach. The sample was drawn using accidental sampling. The sample size for this study was 30. The data analysis used the Pearson Product Moment correlation test. The results showed a correlation of 0.512 > 0.361. The results of this study recommend that other researchers who intend to conduct research on the Correlation of Mother's Breastfeeding Techniques to Breast Milk Production. There is a relationship between the two variables which has a positive correlation direction. To involve more samples and variables studied with different designs and use instruments that have standard validity and reliability values.